Influences of the IL-6 cytokine family on bone structure and function. (October 2021) - Sims, Natalie A.
Highlights: Many IL-6 family cytokines and receptors are expressed by cells in bone. IL-6 cytokines stimulate osteoclast formation indirectly through actions on osteoblast-lineage cells. IL-6 cytokines act directly on early progenitors on osteocytes to stimulate bone formation. Mutations in IL-6 family members cause skeletal defects in mice and humans. Abstract: The IL-6 family of cytokines comprises a large group of cytokines that all act via the formation of a signaling complex that includes the glycoprotein 130 (gp130) receptor. Despite this, many of these cytokines have unique roles that regulate the activity of bone forming osteoblasts, bone resorbing osteoclasts, bone-resident osteocytes, and cartilage cells (chondrocytes). These include specific functions in craniofacial development, longitudinal bone growth, and the maintenance of trabecular and cortical bone structure, and have been implicated in musculoskeletal pathologies such as craniosynostosis, osteoporosis, rheumatoid arthritis, osteoarthritis, and heterotopic ossifications. This review will work systematically through each member of this family and provide an overview and an update on the expression patterns and functions of each of these cytokines in the skeleton, as well as their negative feedback pathways, particularly suppressor of cytokine signaling 3 (SOCS3). The specific cytokines described are interleukin 6 (IL-6), interleukin 11 (IL-11), oncostatin M (OSM), leukemia inhibitory factor (LIF), cardiotrophin 1 (CT-1), ciliary neurotrophic factor (CNTF), cardiotrophin-like cytokine factor 1 (CLCF1), neuropoietin, humanin and interleukin 27 (IL-27).